Hybrid Arrangements as Strategic Alliances: Theoretical Issues in Organizational Combinations - Borys, Bryan; Jemison, David B. (Academy of Management Review, 1989)
Hybrid organizational arrangements, in which two or more sovereign organizations combine to pursue common interests, raise significant questions for both scholars and managers. A review of previous research yields four key issues—breadth of purpose, boundary determination, value creation, and stability mechanisms—that form the core of a theory of hybrid arrangements. This theory is then used to generate researchable propositions that explore differences among types of hybrids and to offer insights for managers of hybrid organizations.